F7 and topotecan co-loaded thermosensitive liposome as a nano-drug delivery system for tumor hyperthermia. (1st January 2020) - Du, Chunyang; Li, Shuangshuang; Li, Yuan; Galons, Hervé; Guo, Na; Teng, Yuou; Zhang, Yongmin; Li, Mingyuan; Yu, Peng
Abstract: In order to enhance the targeting efficiency and reduce anti-tumor drug's side effects, topotecan (TPT) and F7 were co-loaded in thermosensitive liposomes (F7-TPT-TSL), which show enhanced permeability and retention in tumors, as well as local controlled release by heating in vitro . TPT is a water-soluble inhibitor of topoisomerase I that is converted to an inactive carboxylate structure under physiological conditions (pH 7.4). F7 is a novel drug significantly resistant to cyclin-dependent kinase but its use was restricted by its high toxicity. F7-TPT-TSL had excellent particle distribution (about 103 nm), high entrapment efficiency (>95%), obvious thermosensitive property, and good stability. Confocal microscopy demonstrated specific higher accumulation of TSL in tumor cells. MTT proved F7-TPT-TSL/H had strongest cell lethality compared with other formulations. Then therapeutic efficacy revealed synergism of TPT and F7 co-loaded in TSL, together with hyperthermia. Therefore, the F7-TPT-TSL may serve as a promising system for temperature triggered cancer treatment.